2017
DOI: 10.1186/s12898-017-0139-7
|View full text |Cite
|
Sign up to set email alerts
|

Wind conditions on migration influence the annual survival of a neotropical migrant, the western yellow-breasted chat (Icteria virens auricollis)

Abstract: BackgroundLong-distance migratory birds in North America have undergone precipitous declines over the past half-century. Although the trend is clear, for many migrating species underpinning the exact causes poses a challenge to conservation due to the numerous stressors that they encounter. Climate conditions during all phases of their annual cycle can have important consequences for their survival. Here, using 15 years of capture-recapture dataset, we determined the effects of various climate factors during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 63 publications
(91 reference statements)
0
9
1
Order By: Relevance
“…Reverse-symmetry models based on site-level data summaries could also be used (Pradel, 1996;Tenan et al, 2014); however, we have encountered long implementation times with these models and difficulty achieving convergence We linked demographic parameters to climate covariates that will be impacted by climate change. Spring winds have been shown to affect survival in other passerine birds (Drake et al, 2014;Huang et al, 2017); however, we found no evidence of spring wind effects on these three Wilson's warbler groups. It is possible that our wind covariate did not properly capture migration conditions due to how migration regions were delineated or that mean tailwind conditions across the entire migration period was not an appropriate metric.…”
Section: Discussioncontrasting
confidence: 89%
See 3 more Smart Citations
“…Reverse-symmetry models based on site-level data summaries could also be used (Pradel, 1996;Tenan et al, 2014); however, we have encountered long implementation times with these models and difficulty achieving convergence We linked demographic parameters to climate covariates that will be impacted by climate change. Spring winds have been shown to affect survival in other passerine birds (Drake et al, 2014;Huang et al, 2017); however, we found no evidence of spring wind effects on these three Wilson's warbler groups. It is possible that our wind covariate did not properly capture migration conditions due to how migration regions were delineated or that mean tailwind conditions across the entire migration period was not an appropriate metric.…”
Section: Discussioncontrasting
confidence: 89%
“…Spring wind conditions may be an important factor affecting survival rates of western Neotropical migrant songbirds (Drake et al, ; Huang et al, ). We calculated a covariate representing average tailwind conditions experienced during spring migration for each overwintering‐breeding region connection.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, warmer temperatures are associated with earlier arrival on the breeding grounds in Ruby-Throated Hummingbirds (Archilochus colubris Linnaeus 1758, Courter et al 2013). In Yellow Warblers (Setophaga petechial Linnaeus 1766, Drake et al 2014), strong westerly winds appear to slow migration and result in a later clutch initiation date, while in the Yellow-Breasted Chat (Icteria virens auricollis Linnaeus 1758, Huang et al 2017), westerly winds are linked to a decline in survival during migration, and a later arrival date at the breeding grounds.…”
Section: Introductionmentioning
confidence: 99%